Ethnobotanic, ethnopharmacologic aspects and new phytochemical insights into Moroccan argan fruits - Khallouki, Farid; Breuer, Andrea; Owen, Robert (International journal of molecular sciences, 2017)
This review summarizes available data on argan fruit botany, geographical distribution, traditional uses, environmental interest, socioeconomic role, phytochemistry, as well as health beneficial effects and examination of future prospects. In particular, ethnomedical uses of argan fruits are carried out throughout Morocco where it has been used against various diseases. Different classes of bioactive compounds have been characterized including essential oils, fatty acids, triacylglycerols, flavonoids and their newly reported acylglycosyl derivatives, monophenols, phenolic acids, cinnamic acids, saponins, triterpenes, phytosterols, ubiquinone, melatonin, new aminophenols along with vitamin E among other secondary metabolites. The latter have already shown a wide spectrum of in vitro, and ex vivo biologicalactivities including antioxidant, anti-inflammatory, anti-diabetic, antihypertensive, anti-hypercholesterolemia, analgesic, antimicrobial, molluscicidal anti-nociceptive and anticancer potential. Argan flesh (pulp) contains a broad spectrum of polyphenolic compounds which may have utility for incorporation into nutraceuticals and cosmeceuticals relevant to the food, cosmetic and health industries. Further research is recommended, especially on the health beneficial effects of the aminophenols.